PENGARUH DIFERENSIASI PERAN DAN TINGKAT PENDIDIKAN TERHADAP KEINGINAN IBU MENGATASI MASALAH LINGKUNGAN KELUARGA - Uswatun Hasanah; Nadiroh Nadiroh (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2017)
The purpose of this research is to determine the influence of role differentiation and education level of the Mother's intention to overcome family problems. The method used in this research is survey with ex post facto approach and a 2x2 factorial design. The sampling technique was multistage sampling. The results of this research are: 1). There is a difference mother’s intention to overcome family problems between the higher education than the lower education, 2).There is a diference in mother’s intention to overcome family problems between clear differentiation than no clear diferentiation, 3). For mothers who have a higher level of education, the intention to overcome family problems will be higher if they have clear role differentiation than no role differentiation, 4). For mothers who have a lower level of education, the intention to overcome family problems will be lower if they have no clear diferentiation of role than a clear differentiation of role, 5) There is an interaction effect between differentiation of role and level of education to intention to overcome family problems.